2008
DOI: 10.1056/nejmoa072685
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Vulvar Intraepithelial Neoplasia with Topical Imiquimod

Abstract: Imiquimod is effective in the treatment of vulvar intraepithelial neoplasia. (Current Controlled Trials number, ISRCTN11290871 [controlled-trials.com].).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
256
1
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 348 publications
(274 citation statements)
references
References 22 publications
12
256
1
5
Order By: Relevance
“…This is in line with previous studies, the focus of which was mainly on T cell infiltrates and LCs/DCs in uVIN in relation to responses to immunotherapy. 5,7,8,16,17,21,43,44 From these studies it was concluded that the epithelium of uVIN lesions was suppressed as it lacked a strong CD81 infiltration and displayed lower numbers of Langerhans cells. 16,17,21 In contrast, the dermis of uVIN lesions was thought to be the most active region as there was abundant infiltration of CD41 and CD81 T cells as well as mature DCs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is in line with previous studies, the focus of which was mainly on T cell infiltrates and LCs/DCs in uVIN in relation to responses to immunotherapy. 5,7,8,16,17,21,43,44 From these studies it was concluded that the epithelium of uVIN lesions was suppressed as it lacked a strong CD81 infiltration and displayed lower numbers of Langerhans cells. 16,17,21 In contrast, the dermis of uVIN lesions was thought to be the most active region as there was abundant infiltration of CD41 and CD81 T cells as well as mature DCs.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] Conventional treatment consistent of potential disfiguring surgical interventions is associated with psychosexual problems and is increasingly replaced by either standardized immunotherapy with imiquimod or immunotherapy in experimental setting by therapeutic vaccination or photodynamic therapy, with promising clinical successes. [2][3][4][5][6][7][8] The incidence of hrHPV-induced dysplasia is increased in immunocompromised patients highlighting the essential role of the immune system in viral clearance. 9,10 Spontaneous regression of HPV is associated with systemic HPV-specific CD41 and CD81 immune responses, however in most of the patients with uVIN these T cell responses are either weak or absent.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, different forms of immunotherapyvaccination to enhance the HPV16-specific T cells response, imiquimod to enhance the local innate immune response, and combination hereof-have been successful in the treatment of HPV16-induced lesions of the vulva. 19,20,43 Similar to HPV-induced lesions of the vulva, the HPV-induced HNSCC are relatively accessible and one could envisage that these strategies might be applicable to tumors of the oropharynx.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of HPV in the diluted samples was determined by genotyping the samples that demonstrated 65 basepair PCR amplimers on a 3% agarose gel using an INNOLiPA Genotyping Extra test (Innogenetics, Ghent, Belgium), according to the manufacturer's instruction. This assay allows the detection of the following HPV types: HPV 6,11,16,18,26,31,33,35,39,40,43,44,45, 51, 52, 53, 54, 56, 58, 59, 66, 68, 69/71, 73 and 74. Hybridization patterns were visually inspected and interpreted using a grid.…”
Section: Hpv Typingmentioning
confidence: 99%